2023
DOI: 10.1108/intr-07-2022-0487
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association between the Proteus effect and intention to play massive multiplayer online role-playing games (MMORPGs)

Seungjong Sun,
Jang Hyun Kim,
Kwan Min Lee
et al.

Abstract: PurposeMassive multiplayer online role-playing games (MMORPGs) are representative metaverse games that are thriving in academia and the industry. This study aims to develop an integrated model based on Yee's motivations and the Proteus effect to explore individuals' intentions of playing MMORPGs.Design/methodology/approachThe data were gathered by conducting an online survey (n = 441) for the players of World of Warcraft, an MMORPG. The collected data were analyzed with a structural equation model.FindingsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…The results reveal that the Proteus effect positively affects users' intention via the mediation of social, immersion, achievement motivations and enjoyment. This study successfully advances the metaverse research pertaining to user experience and online gaming and offers useful guidelines for providers of MMORPGs (Sun et al, 2024).…”
Section: Special Issue Contentsmentioning
confidence: 77%
See 1 more Smart Citation
“…The results reveal that the Proteus effect positively affects users' intention via the mediation of social, immersion, achievement motivations and enjoyment. This study successfully advances the metaverse research pertaining to user experience and online gaming and offers useful guidelines for providers of MMORPGs (Sun et al, 2024).…”
Section: Special Issue Contentsmentioning
confidence: 77%
“…Regarding the opportunities in the metaverse, these articles demonstrate that the metaverse or virtual worlds based on advanced technologies and avatar empowerment may have a beneficial effect on individuals, showing us opportunities offered by the metaverse to carry out a new digital revolution. For example, metaverse provides a realistic environment that facilitates collaboration (Schiller et al ., 2024); the AR technology affords multimodal sensory interaction and enhances purchase intention (Chen et al ., 2024); the Proteus effect induces user engagement and use intention (Sun et al ., 2023); the features afforded by metaverse can satisfy user needs (Zuo and Shen, 2024). At the same time, these articles also provide an initial exploration of the challenges in metaverses.…”
Section: Contributions and Future Directionsmentioning
confidence: 99%
“…In the case of virtual environments, individuals may experience a sense of embodiment and connection with their avatar [2,50], which can lead to the avatar being viewed as an extension of the individual [43]. Through this process of identification and connection with an avatar, individuals may begin merging their physical world self with their virtual world avatar and aligning their behaviours and attitudes accordingly [40]. For example, research on the PE has indicated that individuals who control an avatar of a different gender to their physical world self will alter their behaviour both during and after gameplay to align with pre-existing schema or beliefs regarding that gender [32,52].…”
Section: The Proteus Effectmentioning
confidence: 99%